2013
DOI: 10.1105/tpc.113.114959
|View full text |Cite
|
Sign up to set email alerts
|

HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENES1 Is Required for Circadian Periodicity through the Promotion of Nucleo-Cytoplasmic mRNA Export in Arabidopsis

Abstract: Cold acclimation has been shown to be attenuated by the degradation of the INDUCER OF CBF EXPRESSION1 protein by the E3 ubiquitin ligase HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENES1 (HOS1). However, recent work has suggested that HOS1 may have a wider range of roles in plants than previously appreciated. Here, we show that hos1 mutants are affected in circadian clock function, exhibiting a long-period phenotype in a wide range of temperature and light environments. We demonstrate that hos1 mutants accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 79 publications
5
80
0
Order By: Relevance
“…under this wavelength compared with D. We found that RL inhibits hypocotyl growth in hos1 to a smaller extent than in Col, ;50%, which is consistent with previous observations (MacGregor et al, 2013) and that this phenotype totally depends on a functional PHYB gene because the double mutant hos1 phyB is as insensitive to RL as phyB ( Figures 3B and 3C). These findings suggest that HOS1 participates in the PHYB-dependent pathway that controls hypocotyl elongation under RL conditions.…”
Section: Mutations In Hos1 Affect Several Developmental Processes Regsupporting
confidence: 80%
See 1 more Smart Citation
“…under this wavelength compared with D. We found that RL inhibits hypocotyl growth in hos1 to a smaller extent than in Col, ;50%, which is consistent with previous observations (MacGregor et al, 2013) and that this phenotype totally depends on a functional PHYB gene because the double mutant hos1 phyB is as insensitive to RL as phyB ( Figures 3B and 3C). These findings suggest that HOS1 participates in the PHYB-dependent pathway that controls hypocotyl elongation under RL conditions.…”
Section: Mutations In Hos1 Affect Several Developmental Processes Regsupporting
confidence: 80%
“…MicroRNA 168a/b targets ARGONAUTE1 (AGO1) transcript to regulate AGO1 protein level, which is important for the function of all microRNAs in Arabidopsis. Given that HOS1 can function through both proteolytic and nonproteolytic modes of action, and based on the wide range of genes that are influenced by mutations in the HOS1 gene (MacGregor et al, 2013), it is evident that HOS1 plays versatile roles in gene expression regulation (Jung et al, 2014).…”
Section: The Hos1 Mutation Does Not Further Upregulate Ft Expression mentioning
confidence: 99%
“…3C). A significant increase in the expression of DRAL and other genes involved in nuclear transport, such as RNA EXPORT FACTOR 1 (RAE1) and NUCLEAR EXPORTIN 1B (XPO1B), was recently reported in seedlings of three different NUPdeficient mutants: nup62-2, nup160-1 (a mutant allele of SAR1 not analyzed in our work) (Parry, 2014) and high expression of osmotically responsive genes 1 (hos1) (MacGregor et al, 2013 impaired NPC function and the expression of genes involved in nuclear transport (Parry, 2014). Although it is unclear if this feedback regulation has any biological relevance (e.g.…”
Section: Loss Of Function Of Different Nups Causes An Altered Hypocotmentioning
confidence: 99%
“…S1). More recently, analyses of NUP-deficient mutants, such as hos1, sar1, nua and nup107, also showed disrupted circadian function and coldregulated gene expression, suggesting that these additional phenotypes are also a general consequence of disrupting NPC function in plants (MacGregor et al, 2013). Our analyses indicated that some of these mutants share additional phenotypes, such as upregulation of DRAL expression, long hypocotyls under W and/or attenuated hypocotyl elongation in response to simulated shade (Figs 1-3, Figs S5, S6).…”
Section: Dra2-1 Seedlings Display An Attenuated Early Induction Of Pamentioning
confidence: 99%
See 1 more Smart Citation